1989
DOI: 10.2466/pr0.1989.65.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Attributions for Problems and Solutions in College Students

Abstract: 50 adult clients at college counseling centers completed scales measuring depression, attributions for their primary problem and its expected improvement, and locus of control. Subjects who were more depressed made relatively internal and stable attributions for their primary problems, were less likely to believe they would improve, and expressed more belief in the importance of chance and powerful others. As a group, subjects tended to view their improvement as more internal and controllable than the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies examining the concurrent relation between attributions for real events and depression have shown differences between depressed and nondepressed individuals on the globality and stability dimensions but not on the locus dimension (e.g., Barthe & Hammen, 1981;Cochran & Hammen, 1985, sample 2;Gong-Guy & Hammen, 1980;Hammen, Krantz, & Cochran, 1981). In a longitudinal study, Firth and Brewin (1982) examined attributions for recent negative life events, and found that depressed patients who attributed these events to global and stable factors were more depressed 6 weeks later (see also Endlich, 1989). Similar results were found with students' attributions for exam performance (e.g, Kayne, Alloy, Romer, & Crocker, 1986).…”
mentioning
confidence: 86%
“…Studies examining the concurrent relation between attributions for real events and depression have shown differences between depressed and nondepressed individuals on the globality and stability dimensions but not on the locus dimension (e.g., Barthe & Hammen, 1981;Cochran & Hammen, 1985, sample 2;Gong-Guy & Hammen, 1980;Hammen, Krantz, & Cochran, 1981). In a longitudinal study, Firth and Brewin (1982) examined attributions for recent negative life events, and found that depressed patients who attributed these events to global and stable factors were more depressed 6 weeks later (see also Endlich, 1989). Similar results were found with students' attributions for exam performance (e.g, Kayne, Alloy, Romer, & Crocker, 1986).…”
mentioning
confidence: 86%
“…Personal control refers to the perceived power an individual has in an event, and external control refers to how much influence a source outside the individual is perceived to have in an event. Endlich (1989) used Weiners (1985 theory as a framework for studying the attributions that depressed clients make for the causes of and solutions to their problems. Fifty clients from a college counseling center completed the Beck Depression Inventory (Beck & Steer, 1987) and the Causal Dimension Scale (Russell, 1982), which was used to measure attributions of internality, stability, and controllability for both problem cause and solution.…”
Section: Weiners Theory Of Attributionsmentioning
confidence: 99%
“…Unlike other attribution theories, Brickman et als theory accounts for beliefs about not only the cause of a problem but also its solution. Because problem solving is such a central component to counseling, Brickman et als theory has been judged to be important to both the process and the outcome of counseling (Atkinson, Worthington, Dana, & Good, 1991;Endlich, 1989;Karuza, Zevon, Rabinowitz, & Brickman, 1982;McCracken, Hayes, & Dell, 1997;Tracey, 1988;Worthington & Atkinson, 1993, 1996. Brickman et als (1982) theory describes a four-cell taxonomy (i.e., four models) of high and low responsibility attributions for the causes of and solutions to problems.…”
mentioning
confidence: 99%